KEPIMPINAN BERDASARKAN KECERDASAN HATI DALAM ISLAM - Muhammad Khairi Mahyuddin (Jurnal Teknologi Pendidikan Madrasah, 2018)
Leadership in human life is Fitrah. In Islam, leadership is heavy assignment and hard responsibility at now and hereafter. Leadership based on heart is leadership based on tauhid and makrifah. This is Islamic leadership which has be done by Rasulullah, S. A. W, his sahabah, and slaf soleh. They have getted a glory in leading a ummat on all aspect of human life, building a tamaddun and have a certain character. In this context, leadership in Islami College in Celebes (Sulawesi), were need to inspire. Islamic doctrine can not to be stand up, without leadership of commander which have strategy and structural knowledge. Result of integrated leadership basedn on heart and workship all element of society, Islamic College would be good development and be center to necessity rohani (roh), and jasmani (body).